Para una historización de la relación entre cine y memoria. Las producciones sobre la dictadura de Pinochet (fines de los 70 e inicios de los 80) - Marcy Campos Pérez (Amnis)
The aim of this paper is to understand and situate historically the relationship between memory and cinema, focusing on the discourse associated with the audiovisual productions about the Chilean dictatorship. We will use a corpus that considers interviews with filmmakers, analysis of exile films and productions made inside Chile, contained in publications of the same period. In the first part, we analyze the discourses associated with the Chilean cinema of exile and in a second part, those referring to the audiovisual production made in Chile in the early 80s.